Rainforest animals - Hess, Paul. (New York : De Agostini Editions : Distributed by Stewart, Tabori & Chang, 1996)
Introduces some of the animals that live in tropical rain forests in illustrations and brief poems by a variety of poets.
Ages 18 months and up.
Keywords: Rain forest animals -- Juvenile poetry; Children's poetry, American; Rain forest animals -- Poetry; Animals -- Poetry; American poetry -- Collections